1999
DOI: 10.1016/s0042-6989(98)00212-0
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention modifies spectral sensitivity of nystagmic eye movements

Abstract: If we look out of the window of a travelling train our eyes move rapidly back and forth (saccadic movement). With no attention to individual objects, gaze velocity is low but nystagmic frequency is high (stare nystagmus). If we are interested in individual objects, the angular velocity of gaze is high and the nystagmic frequency low (look nystagmus) (Ter Braak, J.W.G. (1936). Untersuchungen ueber optokinetischen Nystagmus. Archives Néerlandaises de Physiologie de L'homme et des Animaux, 21, 309-376). We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…For example, chicks are unable to detect texture boundaries if the luminance of the two textures is matched for the D-cones, implying that these cones are specifically used for this task (Jones & Osorio, 2004); because the D-cones have a broad spectral sensitivity they might be particularly suited for detecting small changes in luminance but unsuited to color discrimination. There is also evidence that in humans there are two types of optokinetic nystagmus: one in which S-cones are used, and one in which they are not (von Campenhausen & Kirschfeld, 1999), while in the zebra fish S-cones are used for phototaxis, but not for optokinetic nystagmus (Orger & Baier, 2005). Furthermore, the primate superior colliculus does not receive retinal inputs from S-cones (Derrington, 2002), and it is asserted that the phenomenon of the saccadic remote distractor effect is blind to visual inputs received by these cones (Sumner, Nachev, Vora, Husain & Kennard, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, chicks are unable to detect texture boundaries if the luminance of the two textures is matched for the D-cones, implying that these cones are specifically used for this task (Jones & Osorio, 2004); because the D-cones have a broad spectral sensitivity they might be particularly suited for detecting small changes in luminance but unsuited to color discrimination. There is also evidence that in humans there are two types of optokinetic nystagmus: one in which S-cones are used, and one in which they are not (von Campenhausen & Kirschfeld, 1999), while in the zebra fish S-cones are used for phototaxis, but not for optokinetic nystagmus (Orger & Baier, 2005). Furthermore, the primate superior colliculus does not receive retinal inputs from S-cones (Derrington, 2002), and it is asserted that the phenomenon of the saccadic remote distractor effect is blind to visual inputs received by these cones (Sumner, Nachev, Vora, Husain & Kennard, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Campenhausen found that individuals who focused on a single stimulus experienced a significant increase in eye velocity and a decrease in look nystagmus [ 39 ]. Studies have shown that eye movement indices such as peak sweep speed and blink frequency are related to the attentional control process [ 40 ].…”
Section: Statistical Results and Analysismentioning
confidence: 99%
“…In bees, the long-wavelength photoreceptors are thought to be responsible for luminance vision (Backhaus, 1991;Giurfa et al, 1997; but see Ng et al, 2018), while primates sum the output of the medium and long-wavelength sensitive cones (Whittle, 1986;Osorio & Vorobyev, 2008). Birds segregate achromatic and chromatic signals by allocating single cones to colour perception and use double cones in luminance perception (v. Campenhausen, Kirschfeld, Campenhausen, & Kirschfeld, 1998;Osorio, Mikló, et al, 1999;Osorio & Vorobyev, 2005). Fish may use individual or summed output of the medium or long-wavelength cones (Neumeyer, Wietsma, & Spekreijse, 1991;Siebeck et al, 2014); however, this is not clear.…”
Section: Luminance Perceptionmentioning
confidence: 99%